5-Bis-(2,6-difluoro-benzylidene) Cyclopentanone Acts as a Selective 11β-Hydroxysteroid Dehydrogenase one Inhibitor to Treat Diet-Induced Nonalcoholic Fatty Liver Disease in Mice - Guan, Hongguo; Wang, Yiyan; Li, Huitao; Zhu, Qiqi; Li, Xiaoheng; Liang, Guang; Ge, Ren-Shan (Frontiers in Pharmacology, 2021)
Background: 11-Hydroxysteroid dehydrogenase 1 is responsible for activating inert glucocorticoid cortisone into biologically active cortisol in humans and may be a novel target for the treatment of nonalcoholic fatty liver disease. Methods: A series of benzylidene cyclopentanone derivatives was synthesized and screened for the selective inhibition of rat, mouse, and human 11-hydroxysteroid dehydrogenase 1 and 2. The most potent compound, [5-bis-(2,6-difluoro-benzylidene)-cyclopentanone] (WZS08), was used to treat nonalcoholic fatty liver disease in mice fed with high-fat-diet for 100 days. Results: WZS08 was the most potent inhibitor of rat, mouse, and human 11-hydroxysteroid dehydrogenase 1, with half maximum inhibitory concentrations of 378.0, 244.1, and 621.1 nM, respectively, without affecting 11-hydroxysteroid dehydrogenase 2 at 100 M. When WZS08 (1, 2, and 4 mg/kg) were gavaged to mice for 100 days, WZS08 significantly lowered serum insulin levels and insulin index at 4 mg/kg. WZS08 significantly reduced the levels of serum triglyceride, cholesterol, low-density lipoprotein, and liver fat ratio as low as 1 mg/kg. It down-regulated Plin2 expression and up-regulated Fabp4 expression as low as 1 mg/kg. It significantly improved the morphology of the nonalcoholic fatty liver. Conclusion: WZS08 selectively inhibits rat, mouse, and human 11-hydroxysteroid dehydrogenase 1, and can treat nonalcoholic fatty liver disease in a mouse model.